( x 2 − 5 x + 5 ) ( x 2 − 1 1 x + 3 0 ) = 1
How many different integers satisfy the equation above?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nicely done. It would be better explain why you chose the 3 particular cases.
Good solution!! But overrated problem.
The values of 72 and 56 you give are wrong; proper values for x 2 − 1 1 x + 3 0 if x = 2 , 3 are + 1 2 and + 6 ; yielding a result, when substituted, of ( − 1 ) e v e n = + 1 For a better explanation of each case, consider a b = 1 . Then, respectively, one of the following conditions must hold: * b = 0 * a = 1 ; or * a = − 1 AND b is an even number. That's why is important to check that the values for the exponent that made the base ( − 1 ) are even numbers
Log in to reply
That is the explanation I totally agree with.
Also you need to check in a^b = 1 that if b=0 then a \neq 0 to avoid indeterminate 0^0
standard solution, upvoted !
I don't understand that when we check for the third case why don't we check for even values of 2 to 30 and then we get solutions of x as 1 to 10 . Where am I wrong ?Basically ,what do you mean by " Then check that x^2 -11 x+30 is even when substitute x by 2 and 3 . By this cases the values of x^2 -11 x+30 are 72 and 56 , respectively".
Is There something Standard ?
But in case 3 it becomes necessary that the power must be even? Please explain case 3
I not able to understand case2
Why two answers will be lost (x=2,3) if you take logarithmn to base 10 on both side of the equation?
I didn't understand case 3. Why -1?
Log in to reply
Case 1, as you know, refers to how any number to the power of 0 equals to 1.
Case 2 comes from how 1 to the power of anything will still equal to 1.
Case 3 is similar to Case 2, except that (-1) to the power of anything EVEN will equal to 1. Therefore, you must check that x 2 − 1 1 x + 3 0 returns an even value when x = 2 or 3.
Log in to reply
Okay. Thankyou Jonathan Yim for this explanation.
only case 2 is true
Log in to reply
All cases are true. Case 1 is true because any number raised to the zeroth power equals 1. Case 2 is true because 1 raised to any power is 1. Case 3 is true because -1 raised to any even power is 1, and it can quickly be verified that for any integer input, the power will always be even for this problem. The final thing to verify in all these cases is that the solutions for the three quadratic a are all indeed integer solutions.
Log in to reply
0 0 is not 1 , so the solution for case 1 needs to exclude that. Making use of this fact would have made this problem a true level 4 or even maybe a level 5 problem.
The LHS will be equal to 1 when either the base=1 ie. x 2 − 5 x + 5 = 1 so x 2 − 5 x + 4 = 0 > > > which gives x=4 and x=1 , Or when the power is 0 ie. x 2 − 1 1 x + 3 0 = 0 > > > x 2 − 5 x − 6 x + 3 0 > > > which gives x=5 and x=6 , Or when the base is(-1) and the power is even so x 2 − 5 x + 5 = − 1 > > > x 2 − 5 x + 6 = 0 which gives x=2 and x=3 but x=2 and x=3 on substituting in the power should be even which is true hence x={1,2,3,4,5,6} hence 6 is the answer, also in the second case notice that the base has will be equal to 0 only for irrational values so the situation 0 0 can never occur for integer values
Their are basically three cases in which the result will be 1 ie. a n = 1 if Case 1 a=any integer and n is zero Case 2 a=1 and be any integer Case 3 a = − 1 and n is even integer Now let us proceed towards our problem Case 1: when x 2 − 1 1 x + 3 0 = 0 Or ( x − 6 ) ( x − 5 ) = 0 Ie. x = 6 , 5 Case 2: when x 2 − 5 x + 5 = 1 Or ( x − 4 ) ( x − 1 ) = 0 ie. x = 4 , 1 Case :3 when x 2 − 5 x + 5 = − 1 Or ( x − 2 ) ( x − 3 ) = 0 ie. x = 3 , 2 ∗ ∗ n o t e ∗ ∗ this case is only valid when value of the power is even,ie. When x 2 − 1 1 x + 3 0 is even. Let us see whether x 2 − 1 1 x + 3 0 = 0 is even or not,here when x is even then ( e v e n ) 2 − ( e v e n ) + ( e v e n ) is always a even now in case of odd ( o d d ) 2 − ( o d d ) + ( e v e n ) will again always even, so all the above 3 cases are are verified hence their are 6 values for which the above expression helds true which are x = 1 , 2 , 3 , 4 , 5 , 6 so the answer is 6
3 cases are possible for the question :
Case 1 :
We know that 1 x = 1 for any real x .
Hence, setting x 2 − 5 x + 5 = 1 ,
x 2 − 5 x + 4 = 0
( x − 4 ) ( x − 1 ) = 0
x = 1 , 4
Case 2:
We know that x 0 = 1 for any x except 0
Setting x 2 − 1 1 x + 3 0 = 0 , we get
( x − 5 ) ( x − 6 ) = 0 .
x = 5 , 6
Case 3:
( − 1 ) n = 1 for even n .
Therefore, in addition to putting x 2 − 5 x + 5 = − 1 , we also need to check if x 2 − 1 1 x + 3 0 is even.
x 2 − 5 x + 6 = 0
( x − 2 ) ( x − 3 ) = 0
x = 2 , 3
Substitution 2 and 3 in x 2 − 1 1 x + 3 0 , we notice that in both cases, it comes out to be even.
Hence, 6 integers satisfy the given equation.
There are 3 different ways you can achieve 1. x^2-5x+5=1 2. x^2-11x+30=0 3. x^2-5x+5=-1 and x^2-11x+30= multiple of 2. Quadratic cases 1 and 2, you get 6, 5, 4, 1. For the last, you get 3 and 2 for x^2-5x+5=-1, and to confirm these you need to subtract from 121 to make the square of 5 and the square of 7. Subtract squares of 7 and 5 from 121, and you find that the result is divisible by 4.
1, 2, 3, 4, 5, 6 all work.
We'll denote the above expression as a^b=1. There are 3 cases to make the expression true. either: a = 1 (1 to any power will be 1) b = 0 (numbers to power of 1 will be 1) or a = -1 (as long as b is even) hence: x^2 -5x +5 = 1 x=1 or x=4 [these are two integers here] then: x^2-11x+30=0 x=6 or x=5 [these are two integers here] and: x^2-5x+5=-1 x=2 or x=3 [two integers*] since -1 to an even power is 1, we plugin our integer values into "b" and check that both integers make the case true.
As a total there are 6 different integers that satisfy the equation.
Problem Loading...
Note Loading...
Set Loading...
Case 1:
x 2 − 1 1 x + 3 0 = 0
( x − 5 ) ( x − 6 ) = 0 ⇒ x = 5 , 6
Case 2:
x 2 − 5 x + 5 = 1
x 2 − 5 x + 4 = 0
( x − 1 ) ( x − 4 ) = 0 ⇒ x = 1 , 4
Case 3:
x 2 − 5 x + 5 = − 1
x 2 − 5 x + 6 = 0
( x − 3 ) ( x − 2 ) = 0 ⇒ x = 2 , 3
Important
Then check that x 2 − 1 1 x + 3 0 is even when substitute x by 2 and 3 . By this cases the values of x 2 − 1 1 x + 3 0 are 7 2 and 5 6 , respectively.
∴ x = 1 , 2 , 3 , 4 , 5 , 6